2017
DOI: 10.1111/bjd.15538
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and high-mobility group box 1 (HMGB1) protein release in vitiligo

Abstract: Linked Article: Kim et al. Br J Dermatol 2017; 176:1558–1568.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…As a classic damage-associated molecular pattern molecule, HMGB1 is involved in the development of many autoimmune skin diseases, including psoriasis (Zhang et al, 2017), atopic dermatitis (Karuppagounder et al, 2015;Wang et al, 2018), and lichen planus (de Carvalho et al, 2018). Recently, some studies have reported that HMGB1 may directly induce the apoptosis of melanocytes in vitiligo (Becatti, 2017;Mou et al, 2018). We found that HMGB1 secreted by melanocytes under oxidative stress was able to promote the secretion of chemokines from keratinocytes, which could induce the cutaneous infiltration of CD8 þ T cells and the maturation of DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a classic damage-associated molecular pattern molecule, HMGB1 is involved in the development of many autoimmune skin diseases, including psoriasis (Zhang et al, 2017), atopic dermatitis (Karuppagounder et al, 2015;Wang et al, 2018), and lichen planus (de Carvalho et al, 2018). Recently, some studies have reported that HMGB1 may directly induce the apoptosis of melanocytes in vitiligo (Becatti, 2017;Mou et al, 2018). We found that HMGB1 secreted by melanocytes under oxidative stress was able to promote the secretion of chemokines from keratinocytes, which could induce the cutaneous infiltration of CD8 þ T cells and the maturation of DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo is a chronic inflammatory disease characterized by skin depigmentation caused by the loss of epidermal melanocytes. The destruction of melanocytes in vitiligo has been attributed to several etiologic theories, including the occurrence of oxidative stress that can directly cause the apoptosis of melanocytes and the generation of CD8 þ cytotoxic T cells that specifically destroy melanocytes (Becatti, 2017;Jian et al, 2014;. Notably, recent studies have demonstrated that oxidative stress facilitates the exposure of self-antigens derived from melanocytes, which are essential for the activation of autoreactive T cells (Xie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, HMGB1 has been well recognized as an important signaling molecule involved in both acute and chronic inflammation process . Its expression was significantly increased in a variety of skin diseases, such as psoriasis, alopecia areata, vitiligo, atopic dermatitis, Henoch‐Schönlein purpura (HSP), pemphigus, and drug‐induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms (DRESS) . Due to the similar pharmacological efficacy to corticosteroids but with milder side effects, Glycyrrhizin has been widely utilized in several dermatologic disorders for many years, such as active‐stage generalized vitiligo, psoriasis, alopecia areata, and is also reported to be effective in alleviating the symptoms of atopic dermatitis and systemic sclerosis in animal model .…”
Section: Discussionmentioning
confidence: 99%
“…All the primary antibodies employed for Western blots were at a 1:1000 dilution. The chemical inhibitors used in this study, U73122 (cat# HY-13419), Gefitinib [28] (cat# HY-50895), and LY294002 [28] (cat# HY-10108), were provided by MedChemExpress (Monmouth Junction, NJ, USA). U73122 is an inhibitor that can specifically inhibit PLC-γ1 phosphorylation at Ser1248 [19,29].…”
Section: Antibodies and Reagentsmentioning
confidence: 99%